2018
DOI: 10.17921/1415-5141.2018v22n1p8-11
|View full text |Cite
|
Sign up to set email alerts
|

Desponte de Cladódios de Pitaia Vermelha de Polpa Branca

Abstract: Atualmente, a diversificação de frutíferas é uma forte tendência para ampliação de oportunidades para o fruticultor. O cultivo da pitaia se tornou importante, tanto para a economia quanto para a saúde, devido ao exotismo de sua aparência, por suas características organolépticas e suas propriedades nutracêuticas. No entanto, informações sobre o cultivo desta frutífera são escassas, necessitando de pesquisas para facilitar seu manejo. Neste sentido, o presente trabalho teve como objetivo avaliar a influência do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
1
3
1
Order By: Relevance
“…The results presented in Table 3 are contrary to those found by [12] in a study with white-pulp pitayas. Such divergence may suggest variations derived from different genetic materials, as well as other conditions such as physiological factors, as well as climatic and nutritional conditions [13].…”
Section: Factorcontrasting
confidence: 96%
“…The results presented in Table 3 are contrary to those found by [12] in a study with white-pulp pitayas. Such divergence may suggest variations derived from different genetic materials, as well as other conditions such as physiological factors, as well as climatic and nutritional conditions [13].…”
Section: Factorcontrasting
confidence: 96%
“…These results may be related to the climatic factor, such as, for Marques et al (2011), temperature, relative humidity and precipitation, which are those that most interfere in the dragon fruit's phenology. Lopez (2010), while evaluating the effect of pruning on the cultivation of dragon fruit, observed that this practice did not influence the number of shoots, as for Ramos et al (2018), corroborating the results obtained in the work. The number of shoots was higher in the red pulp dragon fruit (Figure 5A).…”
Section: Resultssupporting
confidence: 74%
“…Revista Agrogeoambiental, v.15, e20231797, 2023 development of the fruits affected their quality. According toRamos et al (2018), monitoring annual precipitation is extremely important, because in the absence of rainfall, irrigation is fundamental for productivity and fruit quality. In addition, excessive rainfall during flowering can cause flower buds to fall and influence fruit quality.…”
mentioning
confidence: 99%
“…Potassium increases the pitaya cladode diameter (CAJAZEIRA et al, 2018) and is related to stomatal opening and closure processes, and carbohydrate translocations (MARSCHNER, 2012). According to Laredo (2016), the size and number of buds are important characteristics for pitaya plants; plants that present higher shoot vigor can better capture light and produce photoassimilates, improving the plant nutrition and accumulation of reserves.…”
Section: Rnarmentioning
confidence: 99%